2002
DOI: 10.1152/ajpendo.00566.2001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the vagus nerves in the regulation of basal hepatic glucose production in conscious dogs

Abstract: . Involvement of the vagus nerves in the regulation of basal hepatic glucose production in conscious dogs. Am J Physiol Endocrinol Metab 283: E958-E964, 2002; 10.1152/ajpendo.00566. 2001.-We determined if blocking transmission in the fibers of the vagus nerves would affect basal hepatic glucose metabolism in the 18-h-fasted conscious dog. A pancreatic clamp (somatostatin, basal portal insulin, and glucagon) was employed. A 40-min control period was followed by a 90-min test period. In one group, stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Thus we conclude that the sympathetic efferents play an important role in the regulation of NHGU by exerting a basal inhibitory tone that limits glucose uptake in response to hyperglycemia of peripheral origin. This is consistent with previous work from our laboratory (8), which showed that cooling the vagus nerves (decreasing afferent vagal firing) in the presence of euglycemia and euinsulinemia decreased net hepatic glucose output, presumably by reflexively decreasing the efferent sympathetic outflow to the liver. It is interesting to note that we saw no differences in basal net hepatic glucose output between the two groups in this current study despite hepatic denervation.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Thus we conclude that the sympathetic efferents play an important role in the regulation of NHGU by exerting a basal inhibitory tone that limits glucose uptake in response to hyperglycemia of peripheral origin. This is consistent with previous work from our laboratory (8), which showed that cooling the vagus nerves (decreasing afferent vagal firing) in the presence of euglycemia and euinsulinemia decreased net hepatic glucose output, presumably by reflexively decreasing the efferent sympathetic outflow to the liver. It is interesting to note that we saw no differences in basal net hepatic glucose output between the two groups in this current study despite hepatic denervation.…”
supporting
confidence: 93%
“…Although extensive research has been carried out relating to hepatic afferents and efferents in the euglycemic and hypoglycemic states (8,16,21,22,24,26,34), less is known about the hyperglycemic state, and it remains unclear how the portal signal may be mediated by these nerves. Total hepatic denervation eliminates the ability of the liver to discriminate between portal and peripheral glucose delivery (3), reinforcing the notion that the response to the portal glucose signal is neurally mediated (32,36).…”
mentioning
confidence: 99%
“…At least in mice, these effects can be largely independent of modifications in feeding and body weight. Based on the known importance of the parasympathetic outflow to the liver in regulating glucose production in several different species (56,57), it has been hypothesized that the vagus nerve is an important efferent arm of the nervous system mediating the antidiabetic actions of leptin. For example, the effects of leptin…”
Section: Identification and Segregation Of The Leptin-sensitive Pathwmentioning
confidence: 99%
“…Although extensive research has been carried out relating to hepatic afferents and efferents in the euglycemic and hypoglycemic states [18][19][20][21][22][23][24], less is known about them in the hyperglycemic state. Furthermore, it remains unclear how they are involved in the augmentation of NHGU by portal glucose delivery.…”
Section: Introductionmentioning
confidence: 99%